2020
DOI: 10.1021/acs.langmuir.0c00017
|View full text |Cite
|
Sign up to set email alerts
|

Differential Interactions of Piscidins with Phospholipids and Lipopolysaccharides at Membrane Interfaces

Abstract: Piscidins 1 and 3 (P1 and P3) are potent antimicrobial peptides isolated from striped bass. Their mechanism of action involves formation of amphipathic α-helices on contact with phospholipids and destabilization of the microbial cytoplasmic membrane. The peptides are active against both Gram-positive and Gram-negative bacteria, suggesting easy passage across the outer membrane. Here, we performed a comparative study of these two piscidins at the air–water interface on lipopolysaccharide (LPS) monolayers modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Both Rd and Re-LPS isolation was performed using a modified phenol-chloroform-petroleum ether method following a previously published protocol . Re-LPS was extracted from the D31m4 deep rough (Re) mutant strain of E.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both Rd and Re-LPS isolation was performed using a modified phenol-chloroform-petroleum ether method following a previously published protocol . Re-LPS was extracted from the D31m4 deep rough (Re) mutant strain of E.…”
Section: Methodsmentioning
confidence: 99%
“…Both Rd and Re-LPS isolation was performed using a modified phenol-chloroform-petroleum ether method following a previously published protocol. 42 Re-LPS was extracted from the D31m4 deep rough (Re) mutant strain of E. coli whose core oligosaccharide chain is truncated at the second KDO group. The longer form, Rd -PS, was extracted from a ΔwaaG rough mutant strain of E. coli (CWG303; E. coli F470 with waaG::aacC1 originating from C. Whitfield, University of Guelph) whose LPS inner core extends through HepII.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, only a few studies have been reported in which ternary mixtures of PE, PG, and CL lipids were used. These latter studies focused on the thermotropic behavior of PE/PG/CL mixtures, the structure of the lipid monolayer at the air/water interface, or directly implemented PE/PG/CL mixtures to investigate the activity of an antimicrobial agent. ,, Therefore, a detailed structural and dynamic characterization of PE/PG/CL mixtures is still missing.…”
Section: Introductionmentioning
confidence: 99%